(untitled) (Circe de clásicos y modernos, 2024)
Orphic studies specialists have recently been fortunate due to Giulia Rossetto’s discovery of an unknown hexameter text within a palimpsest, which had Arabic script on its surface. This text stands out for its artificial literary language, typical of the epic tradition, and the presence of direct speech. Its archaic style is characterized by the reuse of Homeric formulas and echoes phrases from various texts, such as the Rhapsodies, Nonnus’ Dionysiaca, and the Orphic Hymns (Rossetto, 2021). The intertextual links between the Sinai hexameters and these texts, especially the direction of their influence, are yet to be established. This paper will detail the codex’s condition, describe the text’s material features, summarize its content, and explore the academic discussion it has ignited.